2022
DOI: 10.3390/ijerph19042259
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental Exposure to Cadmium and Lead on the Risks of Diabetes and Kidney Dysfunction

Abstract: Environmental exposure to cadmium (Cd) or lead (Pb) is independently associated with increased risks of type 2 diabetes, and chronic kidney disease. The aim of this study was to examine the effects of concurrent exposure to these toxic metals on the risks of diabetes and kidney functional impairment. The Cd and Pb exposure levels among study subjects were low to moderate, evident from the means for blood concentrations of Cd and Pb ([Cd]b and [Pb]b) of 0.59 µg/L and 4.67 µg/dL, respectively. Of 176 study subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…The Institutional Ethical Committees of Chulalongkorn University, Chiang Mai University and the Mae Sot Hospital approved the study protocol for the Mae Sot and Bangkok groups. The Office of the Human Research Ethics Committee of Walailak University in Thailand approved the study protocol for the Nakhon Si Thammarat group [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Institutional Ethical Committees of Chulalongkorn University, Chiang Mai University and the Mae Sot Hospital approved the study protocol for the Mae Sot and Bangkok groups. The Office of the Human Research Ethics Committee of Walailak University in Thailand approved the study protocol for the Nakhon Si Thammarat group [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…This study analyzed archived data taken from published reports [ 17 , 18 ]. Ethical review and approval were not applicable.…”
mentioning
confidence: 99%
“…Data were from 603 participants (400 females and 203 males) enrolled in studies conducted in a high-exposure area of the Mae Sot District, Tak Province [ 31 ] and a low-exposure location in Nakhon-Si-Thammarat Province [ 32 ]. As a prospective cohort study in Japan [ 9 ] observed an increased mortality from kidney disease, especially in women, more females were recruited to the present study than males.…”
Section: Methodsmentioning
confidence: 99%
“…This is not applicable for this study which analyzed data taken from authors’ published reports [ 31 , 32 ].…”
mentioning
confidence: 99%
“…Some non-essential metals can show toxic properties, even at low concentrations. Cadmium (Cd) has a long half-life period and carcinogenic effects and is included in group I, according to the international agency for research on cancer [ 4 ]. Lead (Pb) has serious chronic toxicity to organisms and is defined as probably carcinogenic to humans [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%